APLIKASI SISTEM INFORMASI PENJUALAN PADA WARUNG RINDU RASA MALANG - Jayanti Tantiasari H; Sujito (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2024)
Rindu Rasa stall is stall that has stood since 2007. This stall is located at Hamid Rusdi Street No. 1 plot 22, Bunulrejo sub-district, Blimbing village, Malang. The system that was implemented here is still using a manual / traditional metode or with other word is still using the system that has to remember the order. Eventually, foods or beverages that have been ordered not included in the list of payments due to the seller busy serving the next buyer. So when the system is not changed immediately, then it can lead to a loss for stall manager.This application which is made will help stall seller who were in the stall do a recap of sales and income. In addition, this application is also based on desktop that easily used by ordinary users. This application is using Borland Delphi 7 as graphic unit interface. The author uses the Delphi programming language because it’s freeware and the existing components are full compare to the others.